A new approach of a global knowledge-based engineering infrastructure. Issue 3 (16th April 2017) - Salchner, Markus; Hirz, Mario; Stadler, Severin; Ameye, Jonathan
ABSTRACT: The ongoing globalization in almost all markets leads to a wide range of IT-related challenges. Focusing on development processes in mechanical engineering disciplines as they occur in automotive industry, globalization requires a continuously and location-independent provision of software tools and project-oriented data. This involves both supply of a large amount of different commercial software packages for various engineering disciplines as well as handling of large amount of data, configurations, different projects, sites and employee-related information. The broad field of computational design and engineering disciplines within automotive development requires a strong interaction in view of efficient software applications. Especially the CAD-based design phase is characterized by a cooperation of manufacturer and supplier, which often use dissimilar CAD software with different versions or even different vendors. Previous research work focused on development and application of knowledge-based engineering (KBE) applications within a multiple-CAD environment. A method has been proposed for efficient development of KBAs (Knowledge Based Applications), which are able to concurrently support multiple CAD systems and releases. Based on this fundamental approach, the next logical step includes the development of an efficient and secure distribution environment for KBAs. In this context, the present publication introduces a new approach for management and distribution of KBAs, project-related CAD environments and templates, as well as product data quality (PDQ) methods in a worldwide context. GRAPHICAL ABSTRACT: